Long-Term Real-World Effectiveness of Aripiprazole Once-Monthly. Treatment Persistence and Its Correlates in the Italian and Spanish Clinical Practice: A Pooled Analysis - Olivares, José Manuel; Fagiolini, Andrea (Frontiers in Psychiatry, 2022)
Background: One of the most significant risk factors for relapse and hospitalization in schizophrenia is non-compliance to antipsychotic medications, very common in patients with schizophrenia. The aim of this analysis was to evaluate the treatment persistence to aripiprazole once-monthly (AOM) and the factors affecting it in the pooled population of two similar studies performed previously in two different European countries. Methods: Pooled analysis of two non-interventional, retrospective, patient record-based studies: DOMINO and PROSIGO. Both analyzed treatment persistence after starting AOM treatment in the real-world setting. The primary variable was persistence with AOM treatment during the first 6 months after treatment initiation. A multivariate Cox regression model was used to evaluate the influence of several baseline characteristics on the persistence. Results: The study population comprised 352 patients included in the two studies, DOMINO (n=261) and PROSIGO (n=91). The overall persistence with AOM treatment at the end of the 6-month observation period was 82.4%The multivariate analysis showed that patients with ‘secondary school’ level of education present a 67.4% lower risk of discontinuation within 6 months after AOM initiation when compared with ‘no/compulsory education patients’ (p=0.024). In addition, patients with an occupation present a 62.7% lower risk of discontinuation when compared with unemployed patients (p=0.023). Regarding clinical history, patients with a Clinical Global Impression – Severity scale (CGI-S) score ≤3 present a 78.1% lower risk of discontinuation when compared with patients with a CGI-S score ≥6 (p=0.044), while patients with a time since schizophrenia diagnosis ≤8.4 years present a 52.9% lower risk of discontinuation when compared with the rest of patients (p=0.039). Conclusion: The AOM persistence rate observed in this study was 82.4%, which was higher than that reported in clinical trials, aligned with other real-life studies and higher than reported for other long-acting injectable antipsychotics. The persistence rate was high in complex patients, although patients with higher level of education, active occupation, lower initial CGI-S score and shorter time since the diagnosis of schizophrenia appear to be more likely to remain persistent with AOM during the 6 months after initiation.